The interplay of prenatal stress and prenatal depression in Chinese couples: based on the actor-partner interdependence model - Liu, Xiaoqing; Dong, Yuting; Zhou, Jungu; Lin, Shiying; Liu, Minghuan; Zeng, Hang; Zhou, Xiaowan; Song, Yang; Xie, Xiaoxu; Liao, Qiuping; Lin, Shaowei; Wu, Siying (Frontiers in Psychiatry, 2025)
ObjectivePregnant women exhibit heightened stress susceptibility and elevated depression risk during gestation, factors associated with adverse outcomes including postpartum depression. Current research predominantly examines maternal experiences while neglecting spousal influences.MethodsThe study surveyed 282 Chinese married couples using validated scales to assess prenatal stress and depression. And analysed dyadic data from expectant parents using the Actor-Partner Interdependence Model (APIM) to determine the pattern of action of prenatal stress on prenatal depression between couples by calculating the magnitude of the ratio k between the partner effect and the actor effect.ResultsThe analysis revealed k1 = 0.064, 95% CI: (-0.113, 0.260) and k2 = 0.064, 95% CI: (-0.118, 0.249). The confidence intervals for both k1 and k2 included zero, indicating an actor-only pattern in the APIM. Specifically, prenatal stress positively predicted one’s own prenatal depression but did not significantly influence the partner’s depression.ConclusionIt is crucial to encourage couples to actively manage their stress levels during the prenatal period. This can help to reduce the negative psychological effects of prenatal stress, which may lead to improved pregnancy outcomes and postnatal health.